2022
DOI: 10.3389/fmed.2022.1020993
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of coenzyme Q10 and citicoline: A new possibility for patients with glaucoma

Abstract: Glaucoma is the leading cause of irreversible blindness worldwide. Several risk factors have been involved in the pathogenesis of the disease. By now, the main treatable risk factor is elevated intraocular pressure. Nevertheless, some patients, whose intraocular pressure is considered in the target level, still experience a progression of the disease. Glaucoma is a form of multifactorial ocular neurodegeneration with complex etiology, pathogenesis, and pathology. New evidence strongly suggests brain involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…Although specific neurotransmitters, such as the cholinergic drugs, have been used in hypotensive glaucoma treatment (75), less is known about the role of other neurotransmitters in enhancing neuron survival and vision care in glaucoma. It has been recently reported that Coenzyme Q10 (an electron carrier from complexes I and II to complex III, with an essential role in adenosine triphosphate synthesis, and an important antioxidant) and Citicoline (a nootropic agent con numerous beneficial effects in the CNS), eventually combined, in the prevention of glaucoma OND (76). Herein, we have shown that the expression levels of serotonin in plasma samples and aqueous humor were noticeably lower in the POAGG vs. the CG.…”
Section: Discussionmentioning
confidence: 64%
“…Although specific neurotransmitters, such as the cholinergic drugs, have been used in hypotensive glaucoma treatment (75), less is known about the role of other neurotransmitters in enhancing neuron survival and vision care in glaucoma. It has been recently reported that Coenzyme Q10 (an electron carrier from complexes I and II to complex III, with an essential role in adenosine triphosphate synthesis, and an important antioxidant) and Citicoline (a nootropic agent con numerous beneficial effects in the CNS), eventually combined, in the prevention of glaucoma OND (76). Herein, we have shown that the expression levels of serotonin in plasma samples and aqueous humor were noticeably lower in the POAGG vs. the CG.…”
Section: Discussionmentioning
confidence: 64%
“…Для достижения нейропротекторного эффекта при ГНД показано назначение витамина В 3 (Никотинамид) [57], коэнзима Q10 и Цитиколина [58]. Анализ результатов длительного лечения указанными препаратами проводится в настоящее время в ряде многоцентровых исследований.…”
Section: лечениеunclassified
“…Achieving good outcomes in patients with glaucoma and the non-infectious form of uveitis may be challenging for clinicians because of the complex nature of these diseases and delayed definitive diagnosis (Refs 9, 10). Current management of glaucoma includes surgical and pharmacological interventions, both aiming at reducing intraocular pressure (IOP), the primary and only modifiable risk factor associated with the disease, a strategy that has not changed in 100 years (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, IOP control alone is insufficient to halt glaucoma progression in some patients, which, along with high levels of non-compliance, can lead to therapeutic failure and potentially vision loss (Refs 11, 12). Therefore, novel IOP-lowering approaches less dependent upon patient compliance and therapeutic options targeting non-IOP-related risk factors are needed to improve management of glaucoma (Refs 9, 11). Similarly, the standard of care for uveitis has remained the same since the 1950s and relies on immunosuppression by corticosteroids (CS) administered by multiple routes (Ref.…”
Section: Introductionmentioning
confidence: 99%